Adaptive digital precoder codebook resolution for millimeter wave hybrid beamforming - Kuo, Ping-Heng; Ahn, Jaehyun; Mourad, Alain (2017 IEEE 28th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC), 2017)
Hybrid analog-digital beamforming has emerged as an important technique to enable millimeter wave (mmWave) communications in 5G radio access networks. With a two-stage hybrid beamforming procedure, where analog and digital precoders are determined separately and sequentially, the benefits attributed to digital precoding on top of analog beams could be quite marginal in some cases, as sparse propagation paths in a mmWave channel could be well captured by analog beams alone. By exploiting such characteristic, this paper proposes a digital precoder codebook resolution adaptation scheme, wherein a user device is able to determine the digital precoder resolution based on the gain in addition to analog beamforming, in order to reduce feedback overhead without significant performance degradation.